(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
The field experiment was conducted in Jalingo, Nigeria, during the 2019 cropping season to evaluate the effects of varying zinc fertilizer rates on the growth, yield, and quality of Zea mays L. samaz-14 variety. The study utilized a randomized complete block design with five zinc application levels (including a control) and three replications. Application of 7.5 kg Zn ha-1 ha resulted in significant improvements in stem girth, grain yield, and grain weight per cob compared to other treatments. Zinc supplementation enhanced vegetative development, harvest index, and 100-grain weight, leading to increased yield. The yield improvements were attributed to enhanced zinc nutrient availability. The 7.5 kg Zn ha-1 ha rate is recommended as optimal under the study conditions.